Solar Energy in the Winemaking Industry - Smyth, Mervyn; Russell, James; Milanowski, Tony.; SpringerLink (Online service) (London : Springer London, 2011)
Solar Energy in the Winemaking Industry fully documents all aspects of the modern solar winery, beginning with the main drivers (environmental, economic and political) and detailing the current winemaking industry and solar technologies available. It details the various energy demands in the winemaking process from harvest to bottling and beyond. Solar Energy in the Winemaking Industry catalogues the range of wineries globally that have installed a substantial solar collecting system and uses case study material to give the reader an appreciation of the diversity of solar winery facilities. From large industrial-style wineries to boutique family-run wineries; from new state-of-the-art facilities to 15th-century palaces, the application for solar is limitless. The book deals finally with the physical design, installation and operation of the solar system within the winery environment, detailing the equipment, methodologies, processes and concerns that must be addressed in their creation. This presents the reader with a range of solar design and system options, including: generic system type; installation; mounting arrangements; operation; different module and inverter components and configurations; connection; and finance. Owners, managers and planners involved in the design, building or management of a winemaking facility will derive particular benefit from Solar Energy in the Winemaking Industry, but it will also be of interest to anyone with an interest in the wine or solar industries.
1. Introduction to the Solar Winery -- 2. Introduction to Winemaking -- 3. Solar Technology -- 4. Energy Flows in Winemaking Facilities -- 5. Review of Existing Solar Wineries -- 6. Solar Winery Design and Operation.
Keywords: Engineering; Food science; Agriculture; Renewable energy sources; Sustainable development; Engineering; Renewable and Green Energy; Agriculture; Sustainable Development; Food Science; Renewable and Green Energy